Labor Supply within the Firm - Michele Battisti; Ryan Michaels; Choonsung Park (Institute of Labor Economics (IZA), 2023)
There is substantial variation in working time even within employer-employee matches, and yet estimates of the Frisch elasticity of labor supply can be near zero. This paper proposes a tractable theory of earnings and working time to interpret these observations. Production complementarities attenuate the response of working time to idiosyncratic, or worker-specific, shocks, but firm-wide shocks are mediated by preference parameters. The model can be identified using firm-worker matched data, revealing a Frisch elasticity of around 0.5. A quasi-experimental approach that exploits only idiosyncratic variation would find an elasticity less than half this.
Keywords: J22; J31; 330; labour supply; production complementarities; Frisch elasticity